Indonesia’s Energy Relations with the Gulf Cooperation Council Countries: Drivers and Progress - Zulfikar Rakhmat; M Habib Pashya (Indonesian Journal of Energy, 2022)
Located on opposite ends of Asia, Indonesia and the Gulf Cooperation Council (GCC) member states have developed dense and multifaceted relations in recent years. Trade and economic relations have been foundational in developing these ties, with energy playing an important role. Energy has long been at the heart of Indonesia-GCC trade. The relations have expanded from traditional energy such as oil and gas to renewable energy. This article examines the progress of Indonesia-GCC relations, particularly in the energy field. It looks at the major past and present developments in the energy cooperation between Indonesia and the Gulf countries, including exports, imports, as well as investments. In doing so, the paper also examines the drivers behind the growing cooperation.